Analiza stóp zwrotu indeksów giełd w Polsce i na świecie z wykorzystaniem warunkowego rozkładu α-stabilnego i funkcji copula - Papla, Daniel (Analysis of Stock Markets Prices in Poland and Other Countries Using Conditional α-Stable Distribution and Copula Functions, 2005)
This paper presents a trial in using conditional α-stable distribution in the estimation of the real distribution of the chosen stock market returns. To analyse relations between markets were used copula functions, also in the conditional form. First part of paper presents theoretical background of methodology used in research. There are discussed both the α-stable distribution and copula function. Exact methodology is presented in second part. There is described method of changing parameters of stable distribution and copula function to the conditional form in detail. Third part presents results of the empirical research. Data used in research includes indexes from capital markets in Poland, USA, UK, Germany, France, Czech, Hungary and Slovakia. Interpretation of the obtained results concludes the paper.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 423-433